Parathyroid hormone level is associated with mortality and cardiovascular events in patients undergoing coronary angiography - Pilz, Stefan; Tomaschitz, Andreas; Drechsler, Christiane; Ritz, Eberhard; Boehm, Bernhard O.; Grammer, Tanja B.; März, Winfried (European heart journal, 2010)
Elevated parathyroid hormone (PTH) levels have been associated with increased cardiovascular risk in the general population. We aimed to elucidate whether PTH levels are associated with mortality and fatal cardiovascular events in patients referred for coronary angiography.Intact PTH was measured in 3232 Caucasian patients from the LUdwigshafen RIsk and Cardiovascular Health (LURIC) study, who underwent coronary angiography at baseline (1997-2000). During a median follow-up time of 7.7 years, 742 patients died including 467 deaths due to cardiovascular causes. Unadjusted Cox proportional hazard ratios (HRs) (with 95% confidence intervals) in the fourth when compared to the first PTH quartile were 2.13 (1.75-2.60) for all-cause and 2.47 (1.92-3.17) for cardiovascular mortality. After adjustments for common cardiovascular risk factors, these HRs remained significant with 1.71 (1.39-2.10) for all-cause and 2.02 (1.55-2.63) for cardiovascular mortality. Among specific cardiovascular events we observed a particularly strong association of PTH with sudden cardiac death (SCD). The adjusted HR for SCD in the first vs. the fourth PTH quartile was 2.68 (1.71-4.22).Our results among patients undergoing coronary angiography show that PTH levels are an independent risk factor for mortality and cardiovascular events warranting further studies to evaluate whether PTH modifying treatments reduce cardiovascular risk.
Gesehen am 03.05.2023